Induction of Encephalitis in Rhesus Monkeys Infused with Lymphocryptovirus-Infected B-Cells Presenting MOG(34–56) Peptide - Haanstra, Krista G. (Public Library of Science, 2013)
The overlapping epidemiology of multiple sclerosis (MS) and Epstein-Barr virus (EBV), the increased risk to develop MS after infectious mononucleosis (IM) and the localization of EBV-infected B-cells within the MS brain suggest a causal link between EBV and MS. However, the underlying mechanism is unknown. We hypothesize that EBV-infected B-cells are capable of eliciting a central nervous system (CNS) targeting autoimmune reaction. To test this hypothesis we have developed a novel experimental model in rhesus monkeys of IM-like disease induced by infusing autologous B-lymphoblastoid cells (B-LCL). Herpesvirus papio (HVP) is a lymphocryptovirus related to EBV and was used to generate rhesus monkey B-LCL. Three groups of five animals were included; each group received three intravenous infusions of B-LCL that were either pulsed with the encephalitogenic self peptide MOG(34–56) (group A), a mimicry peptide (981–1003) of the major capsid protein of cytomegalovirus (CMVmcp(981–1003); group B) or the citrullinated MOG(34–56) (cMOG(34–56); group C). Groups A and B received on day 98 a single immunization with MOG(34–56) in incomplete Freund’s adjuvant (IFA). Group C monkeys were euthanized just prior to day 98 without booster immunization. We observed self-peptide-specific proliferation of T-cells, superimposed on similar strong proliferation of CD3(+)CD8(+) T-cells against the B-LCL as observed in IM. The brains of several monkeys contained perivascular inflammatory lesions of variable size, comprising CD3(+) and CD68(+) cells. Moreover, clusters of CD3(+) and CD20(+) cells were detected in the meninges. The only evident clinical sign was substantial loss of bodyweight (>15%), a symptom observed both in early autoimmune encephalitis and IM. In conclusion, this model suggests that EBV-induced B-LCL can elicit a CNS targeting inflammatory (auto)immune reaction.